2013
DOI: 10.1177/0883073813480560
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Accidental Overdose of Levetiracetam in an Infant

Abstract: Levetiracetam is one of the new anticonvulsant drugs that has a high therapeutic index and potential antiepileptogenic effects. Herein, we report a patient with multidrug refractory epilepsy and Ohtahara syndrome who was accidentally administered 300 mg/kg/d for 35 days by her mother. To our knowledge, there are only a few cases of accidental overdose of levetiracetam in pediatric patients reported in the literature, and this case study is the first to report such a high and long-term dose in an infant who sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Adverse effects were not observed in infant and children following LEV overdose. 11,12 Sarfaraz et al 13 also detected no neurologic, cardiovascular or gastrointestinal adverse effects in an adult who ingested 600 g LEV and 1.5 g topiramate in a suicide attempt. By contrast, Barrueto et al intubated an adult due to impaired consciousness after ingestion of 30 g LEV and reported a global decrease in DTRs and muscle tone.…”
Section: Discussionmentioning
confidence: 97%
“…Adverse effects were not observed in infant and children following LEV overdose. 11,12 Sarfaraz et al 13 also detected no neurologic, cardiovascular or gastrointestinal adverse effects in an adult who ingested 600 g LEV and 1.5 g topiramate in a suicide attempt. By contrast, Barrueto et al intubated an adult due to impaired consciousness after ingestion of 30 g LEV and reported a global decrease in DTRs and muscle tone.…”
Section: Discussionmentioning
confidence: 97%
“…25 Ozkale et al described in another study that a high dose of 300 mg/kg/d of LEV was given to a patient accidently for 35 days, no side effects were reported in the patient. 26 Shahid Mahmud and Syed Qamar Zaman stated that among children, they found 58% of them with generalized seizure and 32% with focal seizures. 27 Statistics showed that there was significant relation between age group types of seizures (p=0.046); accurate dosage of antiepileptic drugs and seizures management (p=0.007); medication adherence and management of seizures (p=0.007).…”
Section: Discussionmentioning
confidence: 99%
“…Children on polytherapy have a greater risk of adverse events than those receiving monotherapy [22]. Ozkale et al [23] reported an infant who was accidentally administered 300 mg/kg/ d for 35 days by her mother. The patient showed no adverse effects after received a high and long-term dose of levetiracetam.…”
Section: Discussionmentioning
confidence: 99%